Impact of dyslipidemia on 24-h urine composition in adults without urolithiasis - Chao Cai; Zanlin Mai; Tuo Deng; Zhijian Zhao; Wei Zhu; Yaoan Wen; Xiaolu Duan; Wenqi Wu; Guohua Zeng (Lipids in Health and Disease, 2018)
Abstract Purposes To evaluate the influence of dyslipidemia on 24-h urine composition in adults who were non-stone formers (NF). Methods Samples for 24-h urine composition were analyzed from 584 NF adults without urolithiasis in a national six-city-based epidemiologic study. The samples were divided into groups based on total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). The groups were compared based on demographic data and each component of 24-h urinalysis. Results The numbers of participants in high TG, high TC, high LDL, and low HDL were 106, 175, 147, and 59, respectively. The high TG group had increased urinary excretions of oxalate [mean difference (MD) = 0.032 mmol, 95% confidence interval (CI): 0.000–0.065] and potassium (MD = 4.298 mmol, 95%CI: 0.182–8.414). Increased urinary excretion of calcium (MD = 0.531 mmol, 95%CI: 0.061–1.001), sodium (MD = 41.561 mmol, 95%CI: 9.179–73.942), and chloride (MD = 45.209 mmol, 95%CI: 12.118–78.299) were found in the high TC group. Interestingly, the high LDL group had a decreased urinary excretion of calcium (MD = − 0.573 mmol, 95%CI: -1.048 to − 0.097), oxalate (MD = − 0.038 mmol, 95%CI: -0.07 to − 0.006), sodium (MD = − 53.285 mmol, 95%CI: -85.823 to − 20.748), and chloride (MD = − 55.809 mmol, 95%CI: -89.035 to − 22.583). Increased urinary excretions of citrate (MD = 0.455 mmol, 95%CI: 0.076–0.835) and magnesium (MD = 0.697 mmol, 95%CI: 0.244–1.149) were found in the low HDL group. Conclusions The present study first investigated the effects of dyslipidemia on 24-h urinalysis in NF adults. Of note, high LDL and low HDL were found to be adversely related to kidney stone formation. However, people with high TG and high TC should be cautious of getting kidney stones.